2015
DOI: 10.1002/2015gl063270
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crystallographic properties on the ice nucleation properties of volcanic ash particles

Abstract: Specific chemical and physical properties of volcanic ash particles that could affect their ability to induce ice formation are poorly understood. In this study, the ice nucleating properties of size‐selected volcanic ash and mineral dust particles in relation to their surface chemistry and crystalline structure at temperatures ranging from −30 to −38°C were investigated in deposition mode. Ice nucleation efficiency of dust particles was higher compared to ash particles at all temperature and relative humidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…Findings in this study support this, as all five samples contain plagioclase based on XRD results (Figures S4-S8). Other deposition-mode experiments conducted on volcanic ash attribute improved INA to the presence of a crystallographic structure [34], yet two of the samples used here (OB2 and Taupo) are dominated by amorphous glass and show similar values to samples containing higher mineral contents. Thus, results presented here indicate that differences in mineral/glass abundance do not affect depositional INA at the limited range of temperatures investigated (Figure 3).…”
Section: Deposition-mode Ice Nucleation Activitymentioning
confidence: 94%
See 2 more Smart Citations
“…Findings in this study support this, as all five samples contain plagioclase based on XRD results (Figures S4-S8). Other deposition-mode experiments conducted on volcanic ash attribute improved INA to the presence of a crystallographic structure [34], yet two of the samples used here (OB2 and Taupo) are dominated by amorphous glass and show similar values to samples containing higher mineral contents. Thus, results presented here indicate that differences in mineral/glass abundance do not affect depositional INA at the limited range of temperatures investigated (Figure 3).…”
Section: Deposition-mode Ice Nucleation Activitymentioning
confidence: 94%
“…The dotted line represents homogeneous ice nucleation of pure water [53]. "X" symbols denote previous deposition-mode nucleation studies conducted on ash samples from other volcanoes, including Eyjafjallajökull, (Iceland) [34,54], Volcàn Fuego (Guatemala), Taupo (New Zealand), and Soufrière Hills (Montserrat) [37]. Combined with the deposition-mode data obtained here, results of all studies indicate that volcanic ash grains are efficient ice nucleating particles (INPs) at the temperatures examined regardless of bulk composition or mineral content.…”
Section: Deposition-mode Ice Nucleation Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…More recent research by Durant et al [6] has evaluated volcanic ash samples from Chile and Hawaii in the immersion freezing mode giving overall median freezing temperatures of 253.1 K. They also investigated the effects of composition and surface area on the ice nucleating efficiencies of volcanic ash, but found only a weak correlation with freezing temperature. Kulkarni et al [17] has suggested that composition is of secondary importance compared to crystallographic structure regarding the ice nucleating efficiency of volcanic ash. Fornea et al [18] determined an average freezing temperature of 254.9 ± 2.0 K for large ash particles (250–300 μm) immersed in droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Durant et al (2008) showed that compared to similar meteorological clouds, enhanced ice crystal concentrations and smaller average ice size may be expected in volcanic clouds. However, the "specific chemical and physical properties of volcanic ash particles that could affect their ability to induce ice formation are poorly understood" (Kulkarni et al, 2015).…”
Section: Introductionmentioning
confidence: 99%